Modern management and supervision of financial institutions - Poshyanandra, Kovit ed. (ASEAN BangkokTH, 1992)
Includes papers on development of financial structures; ASEAN country studies on regulation and supervisory provisions in their financial systems; and international regulatory and supervisory practices.